Business Ethics in Moderating the Relationship Between Sustainability Governance and Digital Transformation on Firm Performance - Darmawan, Arya; Khomsiyah; Aryati, Titik (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In the face of escalating global and domestic challenges, sustainability governance has emerged as a critical corporate priority, reflecting the growing demand for organizations to align profitability with environmental responsibility, social accountability, and ethical integrity. This study examines and analyzes the influence of sustainability governance and digital transformation on firm performance, with business ethics as a moderating variable. The sample in this study consists of 156 companies from the basic materials, consumer non-cyclicals, consumer cyclicals, energy, and industrials sectors listed on the Indonesia Stock Exchange during the 2022–2023 period, resulting in 312 observations. This research employs a quantitative approach using panel data regression methods. The findings of this study reveal that the integration of sustainable governance introduced as a novel aspect of this research significantly contributes to improving firm performance. In contrast, digital transformation was found to have no positive impact on firm performance. Furthermore, business ethics is able to strengthen the relationship between sustainability governance and digital transformation on firm performance. This research contributes to the development of stakeholder and agency theories, as well as practical implications for regulators, companies, and society in integrating sustainability and digitalization into corporate governance frameworks.